Cardiovascular toxicity of decabrominated diphenyl ethers (BDE-209) and decabromodiphenyl ethane (DBDPE) in rats. (May 2019) - Jing, Li; Sun, Yanmin; Wang, Yuwei; Liang, Baolu; Chen, Tian; Zheng, Dan; Zhao, Xuezhen; Zhou, Xianqing; Sun, Zhiwei; Shi, Zhixiong
Abstract: Recent reports indicated that decabrominated diphenyl ether (BDE-209) and decabromodiphenyl ethane (DBDPE) exist extensively in the environment. The toxicity of BDE-209 has been reported in quite a few studies, whereas the data of DBDPE are relatively rare. However, databases regarding cardiovascular toxicities of both BDE-209 and DBDPE are lacking. In this study, we investigated the vascular/cardiac trauma induced by DBDPE after oral exposure and compared the results with those of BDE-209 using rat model. Male rats were orally administered with corn oil containing DBDPE or BDE-209 (5, 50, 500 mg/kg/day) for 28 days, then oxidative stress, morphological and ultrastructural changes of the heart and abdominal aorta, levels of creatine kinase (CK) and lactate dehydrogenase (LDH), inflammatory cytokines, endothelin-1 (ET-1), and intercellular adhesion molecule-1 (ICAM-1) in the serum were monitored. Results showed that BDE-209 and DBDPE caused heart and abdominal aorta morphological and ultrastructural damage, serum CK and LDH elevation, and antioxidant enzyme activity changes. BDE-209 and DBDPE-induced inflammation was characterized by the upregulation of key inflammatory mediators, including interleukin-1beta (IL-1β), IL-6, IL-10, and tumor necrosis factor alpha (TNFα). Additionally, BDE-209 and DBDPE led to endothelial dysfunction, as evidenced by the ET-1 and ICAM-1 elevation. Our findings demonstrated that BDE-209 and DBDPE could induce oxidative stress, inflammation, and eventually lead to endothelial dysfunction and cardiovascular injury. Compared to DBDPE, these toxic responses were stronger in the hearts and abdominal aorta of Sprague-Dawley rats exposed to BDE-209. Our findings indicated a potential deleterious effect of BDE-209 and DBDPE on the cardiovascular system. Highlights: Both BDE-209 and DBDPE could cause endothelial dysfunction and cardiovascular injury. Both BDE-209 and DBDPE induced oxidative stress and inflammation response. The cardiovascular toxicity of DBDPE was less severe than that of BDE-209.